Las "jornadas de reflexión teológica" y el desarrollo de un proyecto eclesial posconciliar asociado a la teología de la liberación en el Perú : discurso teológico, redes sociales y cultura eclesial (1969-2000) (Pontificia Universidad Católica del Perú, 2016)
This thesis studies the dissemination and circulation of the Liberation Theology discourse among ecclesiastical actors based on the case study of the Jornadas de Reflexión Teológica (Days of Theological Reflection), a theological formation course prepared by the Departamento de Teología (Theology Department) of the Pontificia Universidad Católica del Perú (Pontifical Catholic University of Peru), between 1971 and 2000. During all these years, the Jornadas constituted an educational project, whose main objective was to provide theological formation to the various actors and ecclesiastical groups that had entered a process of renovation based on the Second Vatican Council (1962-1965) and the Episcopal Conference of Latin America held in Medellin (1968). In this regard, they were a fundamental space of support for the development of a Post Conciliar ecclesiastical project in Peru, where bishops, priests, religious men and women, laymen and laywomen critically reflected on the relationship between their experience of faith, their pastoral practice, and the challenges of the national and ecclesiastical contexts. For this investigation, we used documentary sources of different institutional repositories from Pontificia Universidad Católica del Perú and from ecclesiastic institutions, and we systematized them in databases and electronic card indexes. We supplement the data with the analysis of political and ecclesiastical press and with interviews to the organizers and participants of the “Days”. La tesis estudia la difusión y circulación del discurso de la Teología de la Liberación entre actores eclesiales a partir del caso de las “Jornadas de Reflexión Teológica”, curso de formación teológica preparado por el Departamento de Teología de la Pontificia Universidad Católica del Perú, entre los años 1971 y 2000. Durante sus años de existencia, las “Jornadas” constituyeron un proyecto educativo, cuyo objetivo principal era brindar formación teológica a los diversos actores y colectivos eclesiales que habían entrado en un proceso de renovación a la luz del Concilio Vaticano II (1962-1965) y la conferencia del episcopado latinoamericano en Medellín (1968). En ese sentido, fue un espacio fundamental de soporte al desarrollo de un proyecto eclesial posconciliar en el Perú, donde obispos, sacerdotes, religiosos (as) y laicos (as) reflexionaban críticamente sobre la relación entre su experiencia de fe, su práctica pastoral y los desafíos del contexto nacional y eclesial. Para la investigación, utilizo fuentes documentales de distintos repositorios institucionales de la PUCP y de instituciones eclesiales, las cuales han sido sistematizadas en bases de datos y ficheros electrónicos. Complemento la información con la revisión de prensa política y eclesial, y con entrevistas a los organizadores y participantes de las Jornadas.